Mitigating dysfunctional audit behavior: analysis of organizational commitment, auditor performance, and turnover intention / Rizqa Anita ...[et al.] - Anita, Rizqa; Abdillah, Muhammad Rasyid; Anugerah, Rita; Zakaria, Nor Balkish (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2018)
Public accounting firms are expected to increase audit quality with mitigating dysfunctional behavior. Understanding what causes dysfunctional audit behavior is critical for public accounting firms. The purposes of this study are to investigate the effects of organizational commitment on auditor acceptance of dysfunctional audit behavior through turnover intention and auditor performance. The Partial Least Square analysis was applied to a questionnaire survey data from 129 auditors working in public accounting firms in Sumatera Island (Indonesia). results indicate that auditors who are more accepting of dysfunctional audit behavior tend to possess an exhibit higher turnover intention, report lower level of auditor performance and weak organizational commitment. Further analysis found that turnover intention and auditor performance mediate the effect of organizational commitment on auditor acceptance of dysfunctional audit behavior.